Longitudinal molecular analysis of clinical and fecal Escherichia coli isolates at a Veterans Affairs Medical Center in Minnesota, USA, 2012–2019 - Clabots, Connie; Thuras, Paul; Johnson, James R. (Frontiers in Microbiology, 2024)
Introduction Extraintestinal Escherichia coli infections represent a growing public health threat, However, current studies often overlook important factors such as temporal patterns of infection, phylogenetic and clonal background, or the host gut E. coli population, despite their likely significance. Methods In this study, we analyzed >7000 clinical E. coli isolates from patients at the Minneapolis Veterans Affairs Health Care System (2012–2019), and concurrent fecal E. coli from uninfected veterans. We assessed phylogenetic group distribution, membership in selected sequence types (STs), and subsets thereof—including the pandemic, resistance-associated ST131-H30R, and ST1193 lineages—and strain type, as defined by pulsed-field gel electrophoresis. We then analyzed these features alongside the temporal patterns of infection in individual hosts. Results The H30R lineage emerged as the leading lineage, both overall and among fluoroquinolone-resistant isolates, with ST1193 following among fluoroquinolone-resistant isolates. Recurrences were common, occurring in 31% of subjects and 41% of episodes, and often multiple and delayed/prolonged (up to 23 episodes per subject; up to 2655d post-index). Remarkably, these recurrences typically involved the subject’s index strain (63% of recurrences), even when affecting extra-urinary sites. ST131, H30R, ST1193, and fluoroquinolone-resistant strains generally caused significantly more recurrences than did other strains, despite similar recurrence intervals. ST131 strain types shifted significantly over the study period. Infection-causing strains were commonly detectable in host feces at times other than during an infection episode; the likelihood of detection varied with surveillance intensity and proximity to the infection. H30R and ST1193 were prominent causes of fecal-clinical clonal overlap. Discussion These findings provide novel insights into the temporal and clonal characteristics of E. coli infections in veterans and support efforts to develop anti-colonization interventions.